Độ nguy hiểm động đất vùng Nam Bộ và Thành phố Hồ Chí Minh - Xuyên, Nguyễn Đình; Minh, Nguyễn Lê; Hùng, Nguyễn Tiến (Vietnam Journal of Earth Sciences, 2009)
Seismic Hazard assessment of the South Vietnam and Ho Chi Minh City region ...